Sejarah Dan Dinamika Pembangunan Nagari Ambuang Kapua: Tinjauan Kearifan Lokal Dan Potensi Wilayah Otonom - Nurfarhanah; Marisa Revalina; Aisyah Putri; Mely Zamri; Nafisha Azdra Sahira; Afif Abdulhadi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
A dynamics have not been formally documented in written form, posing a risk of distorting the collective memory of the younger generation. This article aims to document the history of the formation of Nagari Ambuang Kapua, analyze the underlying factors behind the lack of historical documentation, and map its potential as an autonomous region. The research method utilized is descriptive qualitative, with data collection techniques consisting of in-depth interviews, observation, and document analysis. The results indicate that the naming and formation of the region were grounded in the principle of "Bulek Aia Dek Pambuluah, Bulek Kato Dek Mufakat" through the traditional council of siriah sakapua at Puncak Guguak. Although officially established as a nagari in 2013, the region is strongly supported by a social structure comprising six main tribes. The primary potential of the nagari lies in the agricultural sector, alongside the local wisdom of Ratik Tulak Bala, which holds significant potential to be developed into religious tourism. This study implies the critical importance of integrating traditional customary laws with modern administration as a foundation for sustainable autonomous regional development